The problem with here is that it's where I'm from : by Jamie Kelly - Benton, Jim (Benton, Jim, 2007)
Jamie Kelly shares with her diary her excitement about the fact that students from Wodehouse Middle School will be going to Mackerel Middle School temporarily.